Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0748233719885565
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure to low-dose bisphenol A induces hyperplasia of dorsolateral prostate and upregulates EGFR expression in adult Sprague-Dawley rats

Abstract: Prostate is sensitive to endocrine hormone level, and the synergetic effect of estrogen and androgen is critical in prostate growth. The change of signal pathways caused by the imbalance of estrogen and androgen might function in the occurrence of prostate diseases. As a well-known endocrine disruptor compound, bisphenol A (BPA) can disturb the normal function of endocrine hormone and affect prostate development. This study aims to investigate effects of BPA on the dorsolateral prostate (DLP) and the related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…As shown in previous studies, BPA contamination is related to development of prostate cancer and elevates centrosome amplification in vitro (78). In another study, BPA caused enlargement of prostate and increased EGFR mRNA level in mature Sprague-Dawley rats when administered orally (79). Another study demonstrated that BPA enhanced human prostate stem cell proliferation (80).…”
Section: The Action Of Bisphenols On Leydig Cells and Prostate Healthmentioning
confidence: 66%
“…As shown in previous studies, BPA contamination is related to development of prostate cancer and elevates centrosome amplification in vitro (78). In another study, BPA caused enlargement of prostate and increased EGFR mRNA level in mature Sprague-Dawley rats when administered orally (79). Another study demonstrated that BPA enhanced human prostate stem cell proliferation (80).…”
Section: The Action Of Bisphenols On Leydig Cells and Prostate Healthmentioning
confidence: 66%
“…Similarly as in breast cancer, the influence of hormones should not be underestimated in PCa. It was observed that BPA alone was not enough to induce a prostate pathology, but it increased the prostate susceptibility to estrogen, thus contributing to carcinogenesis later in life; however, rats exposed to BPA in developmental phases with subsequent testosterone and estradiol treatment showed more relevant results (16), suggesting a possible synergy to induce prostate carcinogenesis (92).…”
Section: Exposure During Prenatal and Postnatal Lifementioning
confidence: 99%
“…Another study evaluated the effects of BPA on adult rats, despite the knowledge that aged rats were prone to develop prostate hyperplasia, and revealed an upregulation of ERα in adult rats (92). A molecular study observed that BPA treatment upregulated the pituitary tumor transforming gene 1, epidermal growth factor, Sh3kbp I and PCNA (92) involved in cell growth and proliferation.…”
Section: Exposure During Prenatal and Postnatal Lifementioning
confidence: 99%
“…Androgens physiologically control growth and functions of the prostate during, but it has been shown that they can also be involved in carcinogenesis [ 81 ]. The interaction among androgens and AR promotes prostate cell proliferation by activating AR-responsive genes and pathways in androgen-dependent adult prostate growth [ 82 , 83 ]. For this reason, AR has a major drug target in BPH [ 83 , 84 ] and PC [ 81 , 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction among androgens and AR promotes prostate cell proliferation by activating AR-responsive genes and pathways in androgen-dependent adult prostate growth [ 82 , 83 ]. For this reason, AR has a major drug target in BPH [ 83 , 84 ] and PC [ 81 , 85 ]. Moreover, it has been demonstrated that estrogens play an important role in male sex hormone secretion as well as in the growth, differentiation, and homeostasis of both normal and cancer prostate cells [ 81 , 86 , 87 ].…”
Section: Introductionmentioning
confidence: 99%